2013
DOI: 10.1037/a0031803
|View full text |Cite
|
Sign up to set email alerts
|

Self-determination, control, and reactions to changes in workload: A work simulation.

Abstract: The objective of this experimental study is to capture the dynamic temporal processes that occur in changing work settings and to test how work control and individuals' motivational predispositions interact to predict reactions to these changes. To this aim, we examine the moderating effects of global self-determined and non-self-determined motivation, at different levels of work control, on participants' adaptation and stress reactivity to changes in workload during four trials of an inbox activity. Workload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 82 publications
4
32
0
Order By: Relevance
“…In fact as suggested by previous studies personal control over the work environment is necessary for individual well-being (Brager et al, 2004;Huang et al, 2004). Empirical studies also have indicated that the availability of choices in the physical environment will lead to better outcomes for employees, such as better performance and improved mood (Paciuk, 1990, Parker et al, 2013, Veitch and Gifford, 1996bGalasiu and Veitch, 2006). Based on the broaden-and-build theory of positive emotions, positive and good feelings change people's bodily systems and predict healthier mental and physical outcomes such as reducing stress and physical pain; it also modify people's perception and insight (Fredrickson, 2001;Fredrickson and Branigan, 2005).…”
Section: The Importance Of Individual Control Over the Physical Work mentioning
confidence: 91%
“…In fact as suggested by previous studies personal control over the work environment is necessary for individual well-being (Brager et al, 2004;Huang et al, 2004). Empirical studies also have indicated that the availability of choices in the physical environment will lead to better outcomes for employees, such as better performance and improved mood (Paciuk, 1990, Parker et al, 2013, Veitch and Gifford, 1996bGalasiu and Veitch, 2006). Based on the broaden-and-build theory of positive emotions, positive and good feelings change people's bodily systems and predict healthier mental and physical outcomes such as reducing stress and physical pain; it also modify people's perception and insight (Fredrickson, 2001;Fredrickson and Branigan, 2005).…”
Section: The Importance Of Individual Control Over the Physical Work mentioning
confidence: 91%
“…Supervisors may provide assistance, for instance, by minimizing the number of project assignments per employee, developing standard operating procedures, and other auxiliary means in order to reduce WDLR. Findings from a recent study suggest that the decent level of control is linked to individual factors such as self-determination (Parker, Jimmieson, & Amiot, 2013). Therefore, decision latitude and decision authority of individual employees should be well balanced and enhanced according to individual competences, particularly in knowledge intensive work processes (Pfaff et al, 2010;Stieler-Lorenz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Trials consisted of 5 emails to be completed within 10-min. Previous research has validated this level of workload and time pressure as representative of moderately high task demands (Parker et al, 2013a(Parker et al, , 2013b. Task instructions conveyed to participants that their objective was to:…”
Section: Inbox Activitymentioning
confidence: 99%
“…The inbox activity used email content developed for previous work simulation experiments by Parker et al (2013a) and Parker et al (2013b). Participants were asked to adopt the role of a HR Manager at a department store, in responding to employee emails.…”
Section: Inbox Activitymentioning
confidence: 99%
See 1 more Smart Citation